Met ACOD meer veroveringen (Antwerpen: De Voorzorg, 1970)
"samenstelling: Leon Lommaert ; bijdragen van Frans Lauwers, Georges Debunne, Louis Melis, Jos Van Eynde, Lode Craeybeckx, Staf Bousson, Frans Detiège, Victor De Bruyne, John Mangelschots, Frans Christiaenssens, Joz. Wijninckx, Eddy De Baere en Frans Block"